2008
DOI: 10.1021/jf800761c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oil Composition in Cultivars and Wild Species of Oat (Avena sp.)

Abstract: Oil quality and content were analyzed in 33 accessions from 13 wild species and 10 accessions of cultivated oat. Wild oat species tended to have higher oil and 18:1 fatty acid (FA) contents and lower amounts of 18:2 and 18:3 FAs as compared to cultivated oats. In addition to common FAs, minor amounts of several hydroxy and epoxy FAs were also present in the oat oil and mainly confined to specific lipid classes. These unusual FAs included the previously reported 15-hydroxy 18:2 (Delta9,12) (avenoleic acid) most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
45
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 27 publications
9
45
1
5
Order By: Relevance
“…However, the levels of estearic and oleic acids were much higher and comparable to Martinez et al [19] reports. Whereas palmitic, linoleic and linolenic acids proportions were in accordance with the research done by Leonova et al [14]. Figure 2 indicates that there were significant (p <0.01) differences between the oat cultivars with respect to their fatty acids composition and distribution (saturated and unsaturated).…”
Section: Number Of Common Bands Sisupporting
confidence: 89%
See 1 more Smart Citation
“…However, the levels of estearic and oleic acids were much higher and comparable to Martinez et al [19] reports. Whereas palmitic, linoleic and linolenic acids proportions were in accordance with the research done by Leonova et al [14]. Figure 2 indicates that there were significant (p <0.01) differences between the oat cultivars with respect to their fatty acids composition and distribution (saturated and unsaturated).…”
Section: Number Of Common Bands Sisupporting
confidence: 89%
“…As the requirements for quality vary with the end use of the crop. Leonova et al reported that interspecific hybridization can be regarded as an efficient source for improving oat grain quality and increasing the nutritional value of the crop for human consumption [14]. And, that the development of oat cultivars with high quality traits in the groat, can be achieved by utilizing wild species in breeding procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Three common fatty acids found in oat seeds, i.e. oleic acid (18:1-9c), linoleic acid (18:2-9c,12c), and linolenic acid (18:3-9c,12c,15c; Leonova et al, 2008) in both free acid and methyl ester forms were used for the activity assay using a previously well-characterized 13-lipoxygenase CsLOX from cucumber (Cucumis sativus) as a positive control (Hornung et al, 1999). The results showed that, similar to the positive control CsLOX13/Rosetta2, AsLOX2/Rosetta2 had high activity toward both linoleic and linolenic free fatty acids, and no activity was observed on either form of oleic acid or methyl ester forms of linoleic acid and linolenic acid.…”
Section: Functional Characterization Of the Oat Putative Lipoxygenasesmentioning
confidence: 99%
“…These fatty acids are mainly present in neutral lipids such as triacylglycerols and diacylglycerols (Leonova et al, 2008;Doehlert et al, 2010). Oat has also been extensively used as an enzyme source to study their biosynthesis, catalyzed by peroxygenase activity (Heimann and Schreier, 1970;Heimann and Dresen, 1973;Hamberg and Hamberg, 1996;Leonova et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation